MORFOMETRIK LAMUN Cymodocea rotundata DI PESISIR PANTAI TANJUNG TIRAM, POKA, TELUK AMBON DALAM - Jessico Hendrick Sermatang (Pattimura University, 2022)
Seagrass is an important resource both ecologically and economically. Morphometric of seagrass and physical chemical parameters of waters can affect by differences in the type of substrate grain size. The aim of this study was to analysis the morphometric characters of seagrass C. rotundata on the physical and chemical parameters of waters and different types of substrates. The research was conducted in February-April 2021 in Tanjung Tiram Coastal Waters, Poka. Seagrass sampling was carried out using purposive sampling method. Data were analysis using variance analysis with SPSS. The results of the research on the physical and chemical parameters of the waters were in the normal range for seagrass growth. The type of substrate in the seagrass habitat of C. rotundata is mud sand and sand. The results of the analysis of anova seagrass C. rotundata showed that there were significant differences specifically total of roots, leaf length, total of leaves and total of vertical nodes